2008
DOI: 10.1007/s00148-008-0215-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling workless measures at the individual and household level. Theory and evidence from the United States, Britain, Germany, Spain and Australia

Abstract: Individual and household based aggregate measures of worklessness can, and do, offer conflicting signals about labour market performance. We outline a means of quantifying the extent of any disparity, (polarisation), in the signals stemming from individual and household-based measures of worklessness and apply this index to data from 5 countries over 25 years. Built around a comparison of the actual household workless rate with that which would occur if employment were randomly distributed over household occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
1
25

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 19 publications
5
51
1
25
Order By: Relevance
“…A more recent literature has suggested that the economic nature of households, and especially the differences between them, has changed markedly in recent decades. Gregg et al (2010) document the conflicting trends between individual and household labour market outcomes for the United States, Britain, Germany, Spain and Australia. In these countries, individual worklessness rates have fallen over the past two decades, while household-based rates have not.…”
Section: Explanations Based On Specific Factorsmentioning
confidence: 99%
“…A more recent literature has suggested that the economic nature of households, and especially the differences between them, has changed markedly in recent decades. Gregg et al (2010) document the conflicting trends between individual and household labour market outcomes for the United States, Britain, Germany, Spain and Australia. In these countries, individual worklessness rates have fallen over the past two decades, while household-based rates have not.…”
Section: Explanations Based On Specific Factorsmentioning
confidence: 99%
“…In the past decade, household joblessness has been raised as a concern in a number of countries due to its association with a wide range of adverse outcomes. In particular, research shows strong links between household joblessness, that is, households where no member is working in the labour market, on the one hand, and poverty and welfare dependence on the other hand (Organisation for Economic Co‐operation & Development, ; Dickens & Ellwood, ; Nickell, ; Gregg et al ., ). Gregg et al .…”
Section: Introductionmentioning
confidence: 97%
“…For the United States, Britain, Germany, Spain and Australia, Gregg et al . () find that individual jobless rates have fallen over the 20 years to 2005 but household‐based jobless rates have not. The study also reveals a few patterns specific to Britain and Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cross-national variation can be remarkable, as will become evident later in the paper (Figure 3). Some results also suggest that joblessness accumulation may be stronger when children are present (Bingley and Walker 2001;Gregg, Scutella and Wadsworth 2004). Furthermore, dual joblessness tends to last longer in households with small children (Härkönen 2007).…”
mentioning
confidence: 99%